PSYCHODRAMA AND PERSONAL DEVELOPMENT - DAN PAŞCA (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia, 2012)
ABSTRACT. Research is a randomized clinical trial conducted on a group of 28 teenagers, mostly aged between 18 and 20 years (11 in experimental sample and 17 in the control sample). Independent variable was the participation/non participation in psychodrama group for personal development and dependent variables: the anxiety, the empathy, the personality traits. It was created and applied a questionnaire to evaluate the behavior of the group leader. Group members have established a hierarchy of Yalom's therapeutic factors, based on their experience in the group.